Yoga Meningkatkan Kualitas Hidup Pada Pasien Kanker: Literature Review - Setiawan, Henri; Nantia Khaerunnisa, Reffi; Ariyanto, Heri; Fitriani, Ade; Anisa Firdaus, Fidya; Nugraha, Davit (Universitas Muhammadiyah Magelang, 2021)
Cancer is a chronic disease that reduces the quality of life of the sufferer. High stressors and low coping due to disease prognosis, therapy management, and minimal social support, have an impact on poor psychological conditions. Therefore, we need complementary therapies such as yoga that is easy, cheap, and can be done independently. Yoga practice increases oxygen supply and relaxes muscles and joints which can increase hormonal work which is beneficial for the body physically and psychologically for cancer patients. Objective: This study aims to explain the effectiveness of yoga on increasing QoL (Quality of Life) in cancer patients. Research data were identified from 5 journal databases including PubMed, JSTOR (Journal Storage), Wiley Online Library, Sage Journal, and Taylor & Francis Online using the PIOS (Participant, Intervention, Outcomes and Study Design) method and MeSH term on advanced search engines. Articles that become research data are articles published in 2006-2020 in the English version, open access, and in full text in the original research article form. A total of 3050 articles were found, a screening process was carried out using the Prisma Protocol to eliminate articles that did not meet the criteria. This literature review study found 16 articles that prove that the use of yoga interventions can improve the quality of life of cancer patients. Cancer patients are advised to do self-care in the form of Yoga to improve their quality of life. Advanced research will need to compare the feasibility between yoga and different intervention.